A retrospective study of 5S behaviours of Physical Activity (PA) among suburban Mumbai population with Type 2 Diabetes Mellitus (T2DM) - Kosha Parikh; Shikha Thosani; Ameya Joshi; Apoorva Hajirnis; Chandani Seth (Journal of Family Medicine and Primary Care)
Background: T2DM is a chronic metabolic disorder to manage the same lifestyle modification is cornerstone. In 2022, the American Diabetes Association (ADA) and the European Association for the Study of Diabetes (EASD) published a consensus report targeting the management of Type 2 Diabetes Mellitus (T2DM), which emphasised the importance of regular aerobic and resistance exercise. Both forms of physical activity (PA) can improve blood glucose, HbA1C levels, flexibility and balance. The ADA and EASD has categorised PA behaviours into 5 S. The 5 S stands for:- Sitting, Stepping, Sleep Sweating, Strengthening. The current study aims at auditing these 5S behaviours in suburban Mumbai population with its impact on HbA1C and body mass index (BMI). Methodology: A Retrospective, questionnaire-based study was conducted in the Endocrinology outpatient department of tertiary care institute in Mumbai suburban district. The demographic details, anthropometric measurements, HbA1C levels, sleep cycle and daily PA schedule including the 5S behaviours were recorded. The data generated was then statistically analysed using the IBM SPSS software v. 23. Results: The study included a total of 356 T2DM participants. Prolong sitting had a statistically significant correlation with BMI (P value = 0.003) and HbA1c levels (P value = 0.001), similarly strength training had a positive correlation with HbA1c (P value = 0.048) as well as with total sleep hours (P value < 0.0001). Behaviour like drowsiness was positively correlated with changing shift duty. Additionally, in the present study, it was also observed that more than half of the study population (55.8%) did not track their daily steps. Conclusion: The findings of the present study emphasize the importance of reducing sedentary time, promoting strength training and enhancing sleep quality in T2DM management. Targeted interventions in these areas can help improve health outcomes and quality of life for T2DM patients.